Impact Of Training On Transferring Livestock Technology For Improvement Of Livelihoods Of The Rural Farmers - Akteruzzaman, M; Miah, MAM; Hossain, MM; Fattah, KA; Rahman, R (Bangladesh Journal of Animal Science, 2012)
The study was carried out to examine the impact of training conducted by Micro- Finance and Technical Support (MFTS) project under Palli Karma Shohayak Foundation (PKSF) for transferring livestock technologies and improving livelihoods of the rural poor in Bangladesh. A total of 632 households were surveyed during April to September 2006 following a multistage stratified random sampling. Evidence showed that both project and non-project beneficiaries were under the primary level of education and their family size was slightly higher (5.3) than the national average. The family members mostly belonged in the working age group (>15 years) indicated a positive feature of engaging in different income generating activities (IGAs). It is evident that the rate and amount of loan was higher with the respondent received training than without training. The rate of adoption of technologies was higher than the level of idea on the concept of housing, feeding, treatment, breeding and marketing. The training beneficiaries improved knowledge on feeding, management and health care of livestock and poultry. Training and demonstration are suggested two strong tools for adoption and dissemination of livestock technology. The herd and flock size increased to the project beneficiaries than non-project beneficiaries. Beneficiaries having training on various IGAs have increased their land area and asset possession to a greater extent in compare to non-project beneficiaries. The housing and sanitation condition of the training beneficiaries was found higher than non-project beneficiaries. The annual income of the training and non-training households increased to 31.22% and 18.20% respectively where the income from different IGAs of livestock was 56.04% and 68.20%. Livestock IGAs were not necessarily price sensitive but more sensitive on nonprice factors such as institutional support, input quality and availability of input. The training thus contributed transferring livestock technologies which ultimately influenced in improving livelihood of the project beneficiaries than the non-project beneficiaries. DOI: http://dx.doi.org/10.3329/bjas.v37i2.9888 BJAS 2008; 37(2): 106-115